TINDAK TUTUR ILOKUSI EKSPRESIF PUBLIC FIGURE ‘RA’ SEBAGAI MC PADA ACARA TIK-TOK AWARDS - Uzlah Ilmi Irwan (Kantor Bahasa Lampung, 2021)
The success of an event largely depends on the MC (Master of Ceremony). A MC is considered professional, if he can communicate well and be able to improvise. The MC also has to recognize what situation and type of program they will bring so that he can choose the right speech when communicating. The existing speech relates to the types of speech acts studied in the field of pragmatics. This study uses a qualitative descriptive method in which the author describes the context and meaning of a video appearance of the MC presenting an event in which the author observes the speech and sees the context of the situation that occurs when the speech takes place. In non-formal events, many types of speech acts are used, one of which is expressive illocutionary speech acts, including expressions of gratitude, praise, congratulations and apologies.Key words: MC, context, meaning, expressive speech